KEEFEKTIFAN MEDIA FLASHCARD DALAM PEMBELAJARAN KOSAKATA BAHASA JEPANG PADA SISWA KELAS X SMAN 9 PEKANBARU - Diningsih, Amelya Putriano; Widiati, Sri Wahyu; Isnaini, Zuli Laili (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study discruses the flashcard media in learning Japanese vocabulary to vocational student SMAN 9 Pekanbaru. The purpose of this study was to determine significant differences, between the vocabulary of student who use the flashcard media and who do not use flashcard media as well as how the vocabulary before and after implementation of flashcard media. The object in this research is second semester of class X student in SMAN 9 Pekanbaru. Cosist of two class, class X Society 1 and X Society 2. This Quasi Experiment using Pretest-Posttest in two classes were experiment’s class and control’s class. The result is the flashcard media can improve the outcomes of Japanese vocabulary better than the outcome with convecional menthod. Experiment class (class treatment) are also increasting with 96,25 to the average value in the experimental class and 61,5 in the control class.Key Word: Learning Vocabulary, flashcard Media , Student of Class X SMAN 9 Pekanbaru